Development of a patient and visitor information kiosk. - Kash-Holley MJ (Journal of Hospital Librarianship, 2008)
This article will help to fulfill the health information needs for patients and visitors in the absence of a consumer health library at Oklahoma State University Medical Center. The target groups for this project were patients and visitors to OSUMC. The kiosk project is a creative solution to the problem of not having a consumer health library, and this article demonstrates that.